A Web Server to Store the Modeled Behavior Data and Zone Information of the Multidisciplinary Product Model in the CAD Systems - Bathla, Yatish; Szenasi, Sandor (Informatica, 2020)
This work focuses on the Human Computer Interaction (HCI) for the multidisciplinary product modeling. Requirement Functional Logical Physical (RFLP) structure has emerged as one of the prominent approaches for modeling the multidisciplinary products. To simplify HCI of a RFLP structured product model, Information Content (IC)provides effective communication and interaction. Though it controls the RFLP level by the Multilevel Abstraction based Self-Adaptive Denition (MAAD) structure. However, it needs a application to represent the modeled behavior data and zone information of an multidisciplinary product model. Further, IC application require a interface to interact with the Computer-Aided Design (CAD) based an multidisciplinary product model application and exchange the information between the database of the servers. As per the knowledge of authors, no work has been done yet on the HCI of the IC. Therefore, this paper propose a Content Web server, where IC application is used to store the modeled behavior data and zone information of the multidisciplinary product model. Then, Content database is created to store the Layer Info-Chunk (LiC) entities information of the multidisciplinary product model. Finally, communication between the Content server and CAD server is done to represent the IC application interface in the multidisciplinary product application. The Apache Tomcat server, PostgreSQL database and RESTful web service are used to implement the operations.